Anti-DNA-IgM Favors the Detection of NET-Associated Extracellular DNA - Wang, Han; Stehr, Antonia; Singh, Jeeshan; Zlatar, Leticija; Hartmann, Arndt; Evert, Katja; Naschberger, Elisabeth; Von Stillfried, Saskia; Boor, Peter; Munoz, Luis Enrique; Knopf, Jasmin; Stürzl, Michael; et al. (International Journal of Molecular Sciences, 2023)
During inflammatory responses, neutrophils enter the sites of attack where they execute various defense mechanisms. They (I) phagocytose microorganisms, (II) degranulate to release cytokines, (III) recruit various immune cells by cell-type specific chemokines, (IV) secrete anti-microbials including lactoferrin, lysozyme, defensins and reactive oxygen species, and (V) release DNA as neutrophil extracellular traps (NETs). The latter originates from mitochondria as well as from decondensed nuclei. This is easily detected in cultured cells by staining of DNA with specific dyes. However, in tissues sections the very high fluorescence signals emitted from the condensed nuclear DNA hamper the detection of the widespread, extranuclear DNA of the NETs. In contrast, when we employ anti-DNA-IgM antibodies, they are unable to penetrate deep into the tightly packed DNA of the nucleus, and we observe a robust signal for the extended DNA patches of the NETs. To validate anti-DNA-IgM, we additionally stained the sections for the NET-markers histone H2B, myeloperoxidase, citrullinated histone H3, and neutrophil elastase. Altogether, we have described a fast one-step procedure for the detection of NETs in tissue sections, which provides new perspectives to characterize neutrophil-associated immune reactions in disease.
CRIS-Team Scopus Importer:2023-03-10
Keywords: anti-DNA-IgM; extracellular DNA; NETs

No NETs no TIME: Crosstalk between neutrophil extracellular traps and the tumor immune microenvironment - Fang, Qi; Stehr, Antonia; Naschberger, Elisabeth; Knopf, Jasmin; Herrmann, Martin; Stürzl, Michael (Frontiers in Immunology, 2022)
The tumor immune microenvironment (TIME) controls tumorigenesis. Neutrophils are important components of TIME and control tumor progression and therapy resistance. Neutrophil extracellular traps (NETs) ejected by activated neutrophils are net-like structures composed of decondensed extracellular chromatin filaments decorated with a plethora of granules as well as cytoplasmic proteins. Many of these harbour post translational modifications. Cancer cells reportedly trigger NET formation, and conversely, NETs alter the TIME and promote tumor cell proliferation and migration. The specific interactions between NETs and TIME and the respective effects on tumor progression are still elusive. In certain tumors, a CD4(+) T helper (Th) 2 cell-associated TIME induces NETs and exerts immunosuppressive functions via programmed death 1 (PD-1)/PD-L1, both associated with poorer prognosis. In other cases, NETs induce the proliferation of Th1 cells, associated with an improved prognosis in cancer. In addition, NETs can drive macrophage polarization and often rely on macrophages to promote cancer cell invasion and metastasis. In turn, macrophages can swiftly clear NETs in an immunologically silent manner. The aim of this review is to summarize the knowledge about the mutual interaction between NETs and TIME and its impact on tumor growth and therapy.
CRIS-Team WoS Importer:2023-01-27
Keywords: adaptive immunity; innate immunity; macrophages; cancer; immunotherapy; tumor microenvironment; neutrophil extracellular traps; neutrophils

Pathological function of neutrophil extracellular traps in human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Tripal, Philipp; Geppert, Carol-Immanuel; Merkel, Susanne; Herrmann, Martin; Stürzl, Michael (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16